P-004 Comparison of mechanical thrombectomy devices in acute stroke intervention: MERCI retriever vs penumbra vacuum aspiration system. (4th July 2012) - Soltanolkotabi, M; Habib, A; Sozzer, A; Shaibani, A; Hurley, M; Miller, J; Bendok, B; Ansari, S
Abstract : Background/Purpose: Stroke is the third-leading cause of death in the USA. Intra-arterial thrombolysis or mechanical thrombectomy has shown promising results in the treatment of hyperacute stroke, but there is no current class 1evidence. Both the MERCI and Penumbra thrombectomy devices have demonstrated near equivalence in single arm trials with respect to the NINDS IV tPA trial, with the benefit of an extended time window for intervention. However, these devices have yet to be juxtaposed to address superiority or sequence of device utilization in a critical time period for intervention. We compared the safety and efficacy of the MERCI and Penumbra devices in the management of hyperacute ischemic stroke patients. Materials and Methods: We retrospectively reviewed a consecutive series of hyperacute ischemic stroke interventions that underwent mechanical thrombectomy with the MERCI and/or Penumbra devices between January 2008 and March 2011. Patient demographics, technical outcomes, complications (ICH-ECASS classification), and clinical outcomes (30-day-NIHSS and 90-day-mRS scores) were recorded. Recanalization success was defined with respect to TICI reperfusion scale scores ≥ 2a. Statistical analysis was performed to study categorical and numerical data using the X 2 and one-way ANOVA tests. Results: Seventy endovascular stroke interventions were treated with MERCI (n=27), Penumbra (n=30), or combination of MERCI/Penumbra (n=13) thrombectomy devices. Subgroups matched in terms of age, gender, and baseline NIHSS. Thromboembolic occlusions were predominantly anterior circulation strokes (94%) with baseline TICI scores of 0/1. Both MERCI and Penumbra devices were not found to be statistically different in terms of successful recanalization, complications, patient outcome, or mortality. We noted a non-statistical trend toward more successful recanalization rates with the MERCI device. However, the increased utilization of IA tPA with the MERCI device could have contributed to higher recanalization success. There were a total of 16(23%) device-related procedural complications. Symptomatic ICH at 24–48 h post-procedure was noted in 5 (7%) of the 70 cases. The overall mortality rate was 8/70 (11%). Device cross-over was attempted in difficult cases, where one device fails to recanalize the vessel, and may have contributed to the lower recanalization rates in the MERCI/Penumbra subgroup. All five operators were inclined to use the Penumbra device in the last 28/32 single device cases due to subjectively lower recanalization times, superior handling or ease of use; however, no objective data for recanalization times was available for comparison due to retrospective limitations. Conclusions: In our single center experience of mechanical thrombectomy devices, we noted no statistical difference in the safety or technical/clinical efficacy of the MERCI or Penumbra systems. Subjective superiority or operator preference may lead to a specific sequence of device utilization, but both devices can be complementary and device crossover may be required to achieve recanalization success in recalcitrant cases. Competing interests: None.